Pengaruh green marketing dan citra merek terhadap keputusan pembelian produk Mcdonald’s di Jakarta Utara - Winata, Jessica; Bernadine; Brastoro (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Global warming increases the awareness of the Indonesian people about the importanceof efforts to preserve the environment. One of the forms is the change in the lifestyle of theIndonesian people to start using ecofriendly products. One of the company that isaggressively implementing the concept of Green marketing is McDonald's Corporation.Moreover, in implementing green marketing, McDonald's Corporation also continuouslyto strive to improve a positive brand image and compete in the market to win the heartsof consumers so that it can influence consumer purchasing decisions. This study aimsto analyze the effect of green marketing and brand image on the purchasing decisions ofMcDonald's products in North Jakarta.This study uses a quantitative method with theobject of research being McDonald's restaurants located in North Jakarta. Data wascollected through the distribution of online questionnaires via Google Form. The dataanalysis techniques used in this study include validity test, reliability test, descriptiveanalysis, classical assumption test and multiple regression analysis, individual parametersignificant test (t test), and coefficient of determination (R2). All data were processed usingthe IBM SPSS Statistics 20 program. This study concluded that green marketing and brandimage have a positive and significant effects on purchasing decisions for McDonald'sproducts in North Jakarta. The suggestions given are to maintaining and increasing theapplication of the green marketing concept and carrying out Corporate SocialResponsibility (CSR) to build a positive brand image.